Creative Thinking Design Model According to Buddhist Principles - Phrommidet, Phramaha Thongsuk; Phra Sutheerattanabundit; Somsri, Toungpetch (Mahachula Academic Journal, 2026)
This article aims to: (1) to study creative thinking design according to modern principles; (2) to study creative thinking design based on Buddhist principles; and (3) to develop a model that promotes creative thinking integrated with Buddhist principles. This qualitative study is a documentary research, employing the analysis and synthesis of data from Buddhist scriptures, academic papers on creative thinking and conceptual design, and neuroscience knowledge. Creative design according to modern principles includes Design Thinking, Creative Thinking, and Critical Thinking. From the study The findings reveal that Buddhist-based creative thinking is holistic and consists of three dimensions: the behavioral dimension linked to Precepts (Sīla), the mental dimension linked to Concentration (Samādhi), and the intellectual dimension linked to Wisdom (Paññā), all of which align with the Threefold Training (Tisikkhā). "Mindfulness" (Sati) serves as a crucial element in establishing the concentration that balances these three dimensions. Furthermore, Buddhist principles for creative thinking design can be synthesized through Yonisomanasikāra-an ingenious and systematic analytical thinking process. The researcher developed a process-based model to promote creative thinking, known as the B-ICT Model , consisting of six steps: (1) Mindful Awareness, (2) Deep Observation, (3) Mindful Analytical Thinking, (4) Creative Ideation, (5) Mindful Prototyping, and (6) Reflective Thinking and Development. This model functions as a continuous cycle, integrating Buddhist principles with the Design Thinking process and neuroscience—specifically Neuroplasticity and Executive Functions. The original contribution of this research is a creative thinking model with "Mindfulness" at its core to govern the thought process. It elucidates the integrated relationship between consciousness, brain function, and creative thinking, leading to the development of innovations that are both novel and ethically grounded. This model can be applied to creative learning, mental and motivational enhancement, cognitive development, and integrated instructional management. It aims to promote holistic human development across five key values: intellectual, mental, behavioral, social, and academic, in alignment with the goals of Buddhist education.